Ligusticum chuanxiong: a chemical, pharmacological and clinical review - Wang, Yin; Wu, Liuyun; Wang, Hulin; Jiang, Mingyu; Chen, Yu; Zheng, Xingyue; Li, Lian; Yin, Qinan; Han, Lizhu; Bai, Lan; Bian, Yuan (Frontiers in Pharmacology, 2025)
Ethnopharmacological RelevanceThe dried rhizome of Ligusticum chuanxiong S.H.Qiu, Y.Q.Zeng, K.Y.Pan, Y.C.Tang and J.M.Xu (Apiaceae; including the horticultural variety Ligusticum chuanxiong Hort.) [synonym: Conioselinum anthriscoides (H.Boissieu) Pimenov and Kljuykov (The taxonomic classification has been adopted by the World Checklist of Vascular Plants)] is a traditional Chinese botanical drug renowned for its anti-inflammatory and antioxidant properties. It has been widely used to treatment various diseases, particularly cardio-cerebral vascular diseases (CCVDs).Aim of the reviewThis review aims to summarize recent advances in Ligusticum chuanxiong (CX) research, including its chemical composition and pharmacological effects, and modern clinical applications.Materials and methodsA systematic literature search was conducted using keywords such as “Chuanxiong,” “traditional Chinese medicine,” “chemical components,” “metabolites,” “CCVDs,” and “pharmacological effects” to identify relevant literature published between 2014 and 2025. Databases including PubMed, Web of Science, Google Scholar, and CNKI were utilized. Chemical structures in SMILES format were retrieved from the PubChem, and two-dimensional chemical structures were generated using ChemDraw Ultra 8.0. Classical prescriptions of chuanxiong were obtained from authoritative traditional Chinese medicine databases.ResultsOver 100 metabolites have been isolated and identified from CX, classified into nine major classes. Key bioactive compounds include senkyunolide A, ligustilide, tetramethylpyrazine (TMP), and ligusticum CX polysaccharides (LCP). CX demonstrates significant pharmacological effects in treating CCVDs, such as atherosclerosis (AS), myocardial and cerebral ischemia-reperfusion injury, and hypertension. Its therapeutic mechanisms include antiplatelet activity, endothelial cell protection, anti-inflammatory, antioxidant, and anti-apoptotic properties. CX can be administered alone or in combination with other traditional Chinese medicines (TCMs) or chemical drugs, showing efficacy in cardiovascular, nervous system, digestive system disorders, as well as analgesia and anticancer activities.ConclusionCX holds substantial clinical value for treating multi-system diseases, with extensive evidence supporting its use in CCVDs. Further research and clinical exploration of CX are warranted to fully harness its therapeutic potential.